2020
DOI: 10.1038/s41591-019-0734-6
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral CD8+ T cell characteristics associated with durable responses to immune checkpoint blockade in patients with metastatic melanoma

Abstract: Immune checkpoint blockade (ICB) of PD-1 and CTLA-4 to treat metastatic melanoma (MM) has variable therapeutic benefit. To explore this in peripheral samples we characterized CD8 + T cell gene expression across a cohort of MM patients receiving anti-PD-1 alone (sICB) or in combination with anti-CTLA-4 (cICB). Whereas CD8 + transcriptional responses to sICB and cICB involve a shared gene set, the magnitude of cICB response is over four-fold greater, with preferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
248
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(278 citation statements)
references
References 44 publications
10
248
1
Order By: Relevance
“…We prespecified four categories of prior PD-1 blockade to characterize the temporal relationship between treatment exposure and diagnosis of COVID-19: ever received PD-1 blockade, most recent dose within 6 months, most recent dose within 6 weeks, and first dose within 3 months. These definitions were selected to examine how recent and more remote exposure to PD-1 blockade might influence COVID-19 severity, cognizant of both the prolonged receptor occupancy that can persist for months (28) as well as the distinct proliferative burst in response to initially starting this therapy (18)(19)(20)(21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We prespecified four categories of prior PD-1 blockade to characterize the temporal relationship between treatment exposure and diagnosis of COVID-19: ever received PD-1 blockade, most recent dose within 6 months, most recent dose within 6 weeks, and first dose within 3 months. These definitions were selected to examine how recent and more remote exposure to PD-1 blockade might influence COVID-19 severity, cognizant of both the prolonged receptor occupancy that can persist for months (28) as well as the distinct proliferative burst in response to initially starting this therapy (18)(19)(20)(21).…”
Section: Resultsmentioning
confidence: 99%
“…As another measurement of robustness, we examined different bio-plausible (19)(20)(21)28) definitions to define the proximity of prior PD-1 blockade exposure. This included those who received PD-1 blockade at any time previously, those in whom the most recent dose of PD-1 blockade was within 6 months of COVID-19 diagnosis, those in whom the most recent dose of PD-1 blockade was within 6 weeks of COVID-19 diagnosis, or who had initiated PD-1 blockade within 3 months of COVID-19 diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NKG7 is one of the most expressed genes in NK cells and is essential for cytotoxic degranulation of NK cells and CD8 + T cells as well as the activation and proin ammatory response of CD4 + T cells [35] . Through mapping T cell receptor cloning, Fairfax et al found that patients who responded to immunotherapy had more CD8 + T cell-related large clones overexpressed gene NKG7 than did non-responders [36] . Although the relationship between GBP5, GZMH, PSMB10 and CD8 + T cells has not been clearly demonstrated in melanoma, some of them have been veri ed in other types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It was speculated that having a high TCR clonal diversity could correlate with higher probabilities to establish efficacious anti-tumor immune responses. Consequently, several studies have indeed associated a better response to a more diverse TCR repertoire in peripheral T cells [60][61][62][63].…”
Section: Future Perspectivesmentioning
confidence: 99%